P-Nitrophenol -Bioremediation using potent Pseudomonas strain from the textile dye industry effluent. Issue 4 (August 2020) - Das, Ananya; Dey, Apurba
Abstract: p-Nitrophenol (PNP) occurs as industrial waste effluents for many industries, including dye & textile and tannery industry, and is the cause of severe health risk to human as well as ecological ones. The limitations of PNP degradation and their pathway remains limited for Indian subcontinent (Eastern India side), climatic and demographic difference from rest of India and the rest of the world. The main aim of the evaluation was to see the efficacy of the isolated strain (Pseudomonas sp JB163 ) for removal of PNP. Optimisation of temperature and pH for the best growth of bacterial strain performed, and then degradation efficiency was checked. The isolate obtained based on 16 srRNA was closely related to Pseudomonas sp showed PNP degradation of more than 90 % up to PNP range of 85 ppm. Optimum temperature & pH for the bacteria to survive was found to be 30 °C & 8.5(slightly alkaline pH). There are many studies throughout the world, which has done phenolic biodegradation using isolated bacteria. However, there are not many studies reported from the eastern part of the Indian subcontinent. Our results suggested that Pseudomonas sp JB163 strain would be a suitable aspirant for bioremediation of nitro-phenolic compounds contaminated sites in the environment on a bigger concentrated scale.